Pengukuran Kadar Ekstraktif dan Sifat Warna pada Kayu Teras Jati Doreng (Tectona grandis) - Ganis Lukmandaru (Fakultas Kehutanan Universitas Gadjah Mada, 2009)
Measurement of Extractive Content and Color properties on Black-streaked Heartwood of Teak (Tectona grandis)Teak (Tectona grandis L.f) in certain areas of Java usually has black streaked heartwood or has been known as